Hubungan antara Fungsi Keluarga dan Kualitas Hidup Lansia - Sutikno, Ekawati (Jurnal Kedokteran Indonesia, 2011)
Background: Family is the smallest unit of a society. Health status of family member is inter-relatedwith various problem faced by other family members. In theory, family function disorder may causehealth problem of the family members. The current increasing number of the elderly leads to problemin the health and function in the elderly. This study aimed to examine the association between familyfunction and the quality of life of the elderly.Methods: This was an analitic-observasional cross sectional study. A sample of 41 old people aged 60years or older was selected from Kelompok Jantung Sehat Surya Group Kediri. The dependent variableunder study was quality of life of the elderly. The independent variable under study was family function.The confounding factor to control for included age, sex, type of family, and employment status. Thevariables were pre-tested for its validity and reliability. The data were analyzed by use of chi squareand multiple logistic regression, on SPSS 17.0.Results: Multiple logistic regression analysis showed that elderly who came from a well-functioningfamily had 25 times higher probalility to have better quality of life than those who came from poorlyfunctioningfamily (OR = 24.9, p = 0.040 ; CI 95% 1.2 to 533.0).Conclusion: Family function has strong positive association with quality of life of the elderly. Familydoctors are recommended to provide information and education to families in order to increasefamily function.Keywords: family function, quality of life, elderly.